A Review of Pedestrian Information Retrieval Research - Xie, Yan; Qu, Jian (INTERNATIONAL SCIENTIFIC JOURNAL OF ENGINEERING AND TECHNOLOGY (ISJET), 2025)
Pedestrian Information Search (PIS) has gained attention for its wide range of practical applications. The main objective of PIS is to find a matching object in a set of scene images or videos. Early work on PIS focused on image-based search. With the advent of deep neural networks, PIS can be freed from the limitations of the search source. Therefore, a systematic study of PIS is necessary. In this paper, we review the research results of PIS based on diﬀerent modalities in terms of the origin of the PIS task, the development history of PIS, and the methods of training and evaluation of PIS models. We selected the better-performing models for experiments. We summarize and comparatively evaluate the experimental results. Finally, we discuss some of the present problems of PIS and some meaningful future research directions.